TETRAPOD REMAINS FROM THE LADINIAN (MIDDLE TRIASSIC) SCELTRICH BEDS OF MONTE SAN GIORGIO UNESCO SITE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
The Sceltrich beds at the base of the upper Meride Limestone (Ladinian) above the Cassina beds, yielded a rich and diversified fish fauna comprising several specimens of the predatory fish Saurichthys and sarcopterygians. Reptile findings instead are scarce and limited to few disarticulated teeth and bones, however, their description can give an, albeit limited, insight about the reptile fauna of the Sceltrich beds which was never documented before, testifiying the presence of large to mid-sized eusauropterygians and of the terrestrial tanystropheid Macrocnemus. The results indicate that the composition of the tetrapod fauna of the Sceltrich beds is similar to that of the upper levels of the Cassina beds. The taphonomic conditions that led to preservation as isolated remains could be due to a combination of different factors most probably involving a disarticulation and loss of elements during a floating phase. However it cannot be excluded that at least in some cases a residence phase of the carcass occurred for enough time to allow decomposition of soft parts, leading to disarticulation and removal of isolated elements by currents.
Keywords: Sauropterygia; Macrocnemus (Tanystropheidae); isolated remains; Ladinian (Triassic); Meride Limestone; description; taphonomy.